Investigation of cytokines, oxidative stress, metabolic, and inflammatory biomarkers after orange juice consumption by normal and overweight subjects - Grace K. Z. S. Dourado; Thais B. Cesar (Food & Nutrition Research, 2015)
Background: Abdominal adiposity has been linked to metabolic abnormalities, including dyslipidemia, oxidative stress, and low-grade inflammation. Objective: To test the hypothesis that consumption of 100% orange juice (OJ) would improve metabolic, oxidative, and inflammatory biomarkers and cytokine levels in normal and overweight subjects with increased waist circumference. Design: Subjects were divided into two groups in accordance with their body mass index: normal and overweight. Both groups of individuals consumed 750 mL of OJ daily for 8 weeks. Body composition (weight, height, percentage of fat mass, and waist circumference); metabolic biomarkers (total cholesterol, low-density lipoprotein-cholesterol [LDL-C], high-density lipoprotein-cholesterol [HDL-C], triglycerides, glucose, insulin, HOMA-IR, and glycated hemoglobin); oxidative biomarkers (malondialdehyde and DPPH•); inflammatory biomarkers (high-sensitivity C-reactive protein [hsCRP]); cytokines (IL-4, IL-10, IL-12, TNF-α, and IFN-γ); and diet were evaluated before and after consumption of OJ for 8 weeks. Results: The major findings of this study were: 1) no alteration in body composition in either group; 2) improvement of the lipid profile, evidenced by a reduction in total cholesterol and LDL-C; 3) a potential stimulation of the immune response due to increase in IL-12; 4) anti-inflammatory effect as a result of a marked reduction in hsCRP; and 5) antioxidant action by the enhancement of total antioxidant capacity and the reduction of lipid peroxidation, in both normal and overweight subjects. Conclusions: OJ consumption has a positive effect on important biomarkers of health status in normal and overweight subjects, thereby supporting evidence that OJ acts as functional food and could be consumed as part of a healthy diet to prevent metabolic and chronic diseases.